2018
DOI: 10.1016/j.jpeds.2018.07.110
|View full text |Cite
|
Sign up to set email alerts
|

Social Adversity and Cognitive, Language, and Motor Development of Very Preterm Children from 2 to 5 Years of Age

Abstract: Objective: To assess the extent to which social and family factors explain variability in cognitive, language, and motor development among very preterm (VPT; <30 weeks of gestation) children from 2 to 5 years of age. Study design: As part of a longitudinal study, VPT children recruited as neonates were assessed at 2 (n=87) and 5 (n=83) years using standardized tests of cognitive, language, and motor ability alongside demographically-matched full term (FT) children (n=63). For VPT children, developmental chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
2
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 57 publications
6
54
2
3
Order By: Relevance
“…Regarding the Hearing and Language quotient, it is relevant to note that most of the infants did not present an index of delay, defined as a score < 1 DS. This result is unexpected and is not in line with previous studies (Cattani et al, 2010;Sansavini et al, 2011;Ballantyne et al, 2016;Ionio et al, 2016;Cheong et al, 2017;de Jong et al, 2017;Lean et al, 2018;Pisoni et al, 2018), in which preterm infants have shown worse linguistic development than FT ones. A possible explanation could regard the time of assessment: all the previously mentioned studies mainly focused on the 2nd year postpartum, while the present study focused on the 1st year postpartum.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Regarding the Hearing and Language quotient, it is relevant to note that most of the infants did not present an index of delay, defined as a score < 1 DS. This result is unexpected and is not in line with previous studies (Cattani et al, 2010;Sansavini et al, 2011;Ballantyne et al, 2016;Ionio et al, 2016;Cheong et al, 2017;de Jong et al, 2017;Lean et al, 2018;Pisoni et al, 2018), in which preterm infants have shown worse linguistic development than FT ones. A possible explanation could regard the time of assessment: all the previously mentioned studies mainly focused on the 2nd year postpartum, while the present study focused on the 1st year postpartum.…”
Section: Discussioncontrasting
confidence: 96%
“…Regarding the Locomotor quotient, ELBW, VLBW and FT babies had similar scores, independently from time of assessment. This result is not in line with previous studies, highlighting that preterm infants, compared to FT ones, had significantly more difficulties in acquiring gross motor skills in the 1st and 2nd year of life (Mukhopadhyay et al, 2010;Fallah et al, 2011;de Souza and de Castro Magalhães, 2012;Ballantyne et al, 2016;Cheong et al, 2017;de Jong et al, 2017;Lean et al, 2018). Regardless, none of these studies differentiated preterm infants in relation to the severity of prematurity.…”
Section: Discussionmentioning
confidence: 58%
“…According to the lexicon size criteria, 24.1% of Italian children born ≤33 weeks28 and 29.4% of French children born ≤34 weeks (Etude épidémiologique sur les petits âges gestationnels (EPIPAGE) 2 study)12 were classified under the 10th percentile of the adapted MCDI-SF based on national normative values, while an absence of word combination was 21.6% 12. Consistent with previous studies,10 12 29 we also found an increasing risk for early language delay among children with higher perinatal risk, defined in our study as lower GA and/or severe neonatal morbidity. Compared with children born at term, children born VPT are at higher risk for atypical brain development, and developmental impairments in various domains 2 3 30.…”
Section: Discussionsupporting
confidence: 88%
“…These infants were recruited as part of a different study that compared longitudinal NDs of infants born very preterm to infants born at term. 18 These term infants were used as the control group for the current study. The infants were admitted to the Well-Baby Nursery at Barnes-Jewish Hospital, and had no history of in utero illicit substance exposure and no evidence of acidosis (defined as pH < 7.20) on umbilical cord or arterial blood gas assessments during the first hour of life.…”
Section: Methodsmentioning
confidence: 99%
“…Parental informed consent was obtained for each subject prior to participation in the study. 18 Data analysis was performed with SPSS software version 21.0 (Chicago, IL) with results reported as mean (SD) or median (interquartile range) and percentage (%). Student's ttest and chi-square test were used for continuous and categorical data, respectively.…”
Section: Methodsmentioning
confidence: 99%